Throughput in macro- and micro-cellular radio systems with multiple correlated log-normal interferers - Şafak, Aysel; Şafak, Mehmet (IEEE, 1994)
The effect of correlation between the desired and/or the interfering signals on the throughput of cellular packet radio systems using slotted ALOHA protocol has been analyzed in the presence of log-normal shadowing and Rayleigh fading. Fading and shadowing improve the capture probability so that the resulting throughput always exceeds the throughput obtained in ideal slotted ALOHA channels. The effect of shadowing on throughput is more dominant than that of Rayleigh fading. The presence of correlation between the packets reduces the throughput significantly compared to the uncorrelated case. The throughput performance of microcellular systems was observed not to differ appreciably from that of macrocellular systems for all practical values of the Rician factor both for coherent and incoherent cumulation of the interferers. The throughput for coherent cumulation of the interferers was shown to be higher than the throughput for the incoherent case.
Proceedings of the 1994 IEEE 44th Vehicular Technology Conference. Part 2 (of 3) --
Keywords: Antennas; Communication channels (information theory); Fading (radio); Network protocols; Packet switching; Probability; Radio interference; Radio receivers; Cellular packet radio systems; Microcellular systems; Poisson statistics; Probability distribution function; Random access protocols; Rayleigh fading; Cellular radio systems